No Country for Women. Women Working in the Italian Music Industry - Paraciani, Rebecca (Italian Sociological Review, 2023)
The article looks at the characteristics of workers in the Italian music industry from a gender perspective. I studied female workers in the Italian music industry, which is analyzed as a male-dominated context. Based on 38 interviews conducted in Italy, this paper investigates female worker participation in the industry in question, stressing the perception of existing gender differences that show how female workers explain inequalities. The discourse analysis of the interviews collected focuses on the characteristics of the interviewees’ jobs, on their perceptions about their relationships with colleagues and on their work role. The study highlights that Italian music industry seems to be “No country for women”. First, there is the existence of “women’s jobs” and “men’s jobs” within the Italian music industry. Secondly, an exclusive club emerges, from which female workers feel they are shut out. Lastly, the distancing of female music workers from “other” women is highlighted, tending to define themselves “super-women”.